What is Ideology? - Jokubaitis, Alvydas (Politologija, 2025)
Researchers of ideologies face unsolvable difficulties in their attempts to define the term. Ideology is a form of statement „x is ideology“ when in place of variable any object can be inserted. The very term ideology is doubtful when it is used to designate the science of ideas. According to Immanuel Kant, science of ideas is impossible because there is no idea of idea. The pretense to explain ideas by reference to other ideas is contrary to their very nature. The definition of ideologies is made even harder by the fact that ideas of reason do not have any adequate referent. This circumstance is what does not allow to transform ideas into objects of empirical knowledge. Ideologies correspond to what Kant in The Critique of Judgment calls aesthetic ideas. These ideas are based on an indirect assignment of symbolic images to principles of reason. Ideologies give sensory images to what can only be grasped by reason. This action, which is of aesthetic character, can turn anything into an object of ideological thinking.
Keywords: ideology; ideas of reason; aesthetic ideas; anthropomorphism; Immanuel Kant